Iranian EFL teachers' attitudes towards teaching methods and materials of high school english textbooks - محمدرضا عطایی; محمد قیطانچیان (Shahid Chamran University of Ahvaz, 2009)
Recently, interest in research on EFL teaching, CLT-based methodology and materials, and post-method pedagogy has gain momentum in the Iranian mainstream education. This study was conducted; 1) to explore EFL teachers' attitudes towards the present EFL methodologies and content of high school textbooks; 2) to examine any probable relationship between teachers' attitudes towards post method pedagogy and their students' achievement; and 3) to probe any correlation between the teachers' instructional experience and their attitudes towards the present teaching methods and materials. To this end, a questionnaire was designed to elicit EFL teachers' beliefs. The subjects were 594 Iranian EFL teachers selected from different cities all over Iran. After the administration of the questionnaire, the data were analyzed through descriptive and inferential statistical procedures. The results indicated that: a) the Iranian EFL teachers hold different patterns of attitudes towards the dominant teaching methods and content of high school English textbooks, b) there is no relationship between the teachers' positive or negative attitudes towards post method and their students' achievement, and c) more experienced teachers' attitudes are different from the attitudes held by less-experienced ones